Tracking data - Baca, A. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
This chapter describes ways of obtaining position data and illustrates their importance in the analysis of team sports. Basic principles for position determination, such as the procedure of trilateration, are presented. Applications in the analysis of the physical demand profile of soccer players and the collective play behavior of basketball players under different given conditions in defensive play underline the potential of tracking data and illustrate the wide range of practical sports applications. The need for adequate validation of position detection systems is pointed out, aspects to be considered in the design of validation studies are highlighted.